The lichens and lichenicolous fungi of the Chalbasy arena in Lower Dnipro sand dunes (Kherson region) (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
160 species of lichens and lichenicolous fungi have been found in Chalbasy arena in Lower Dnipro sand dunes. Absconditella lignicola, Anaptychia crinalis, Bacidia fraxinea, Ramalina canariensis were a new for the Ukrainian plains and Caloplaca monacensis, Chaenotheca chlorella, Cladonia macilenta, Heterocephalacria physciacearum, Lecanora chlarotera, Lepraria lobificans, Porina aenea, Punctelia subrudecta were firsty found for steppe zone. Among Chalbasy arena, the habitats of Burkuty plavni are hotspot for lichens and lichenicolous fungi diversity of the steppe zone of Ukraine. The landscape is cover of 0,5% of Lower Dnipro Sand dunes and has 77% lichens and lichenicolous fungi founding on this territory. The Chalbasy arena represents a northern lichen elements. It occupied of the sand dunes habitats after the last glacial period 10–12 thouthand years ago. Probably, Absconditella lignicola, Candelariella kuusamoensis, Punctelia subrudecta, Usnea glabrescens are relics of the early Holocene. Probably, the penetration of Atlantic species, Anaptychia crinalis, Athallia alnetorum, Bacidia fraxinea, Candelaria pacifica, Ramalina canariensis to the territory of Lower Dnipro sand dunes habitas began in the second half of the Holocene and it continues to this time. In Chalbasy arena, Cetraria aculeata, Ramalina canariensis, Xanthoparmelia camtschadalis are listed in the Red Data Book of Ukraine and Anaptychia ciliaris, Bacidia rubella, Candelaria concolor, Chaenotheca trichialis, Flavoparmelia caperata, Lecania ephredrae, Parmelina quercina, Parmelina tiliacea, Placynthiella olygothropha, Phlyctis argena, Usnea hirta, U. glabrescens are included to the Red List of Kherson region. Absconditella lignicola, Anaptychia crinalis, Athallia alnetorum, Bacidia fraxinea, Candelaria pacifica, Cladonia macilenta, Caloplaca monacensis, Lepra albescens, Chaenotheca chlorinа, Porina aenea, Pseudoschismatomma rufescens, Punctelia subrudecta are vulnerable lichen species within steppe zone and are in need of protection. It is proposed to expand the territory of the Oleshkivski pisky National Park and create a Gileya Regional Landscape Park on western part of Chalbasy arena with aim to protect of the lichen habitats.
Keywords: hotspot lichen diversity, steppe zone, northern elements, Red List, Ukraine.